Entrepreneurship : a study on the foodcourt industry. - Chang, Eric Wee Hua. (2013)
In this project, the project group attempts to develop an understanding of entrepreneurs and the concept of entrepreneurship through entrepreneurs in the foodcourt industry in Singapore. Through the project group’s review of literature on entrepreneurship, we try to arrive at a definition of entrepreneurship which incorporates aspects which are consistently proposed by many writers and is consistent with our understanding of the subject. Our studies also extend to other areas which may affect entrepreneurship such as environmental factors and traits.